Analysis of the population structure of buffaloes in Brazil - dos Santos, Jessica Cristina Gonçalves [UNESP]; da Silveira, Karina Rosa; de Oliveira Seno, Leonardo; Aspilcueta-Borquis, Rusbel Raul; de Araujo Neto, Francisco Ribeiro; Tonhati, Humberto [UNESP] (Springer Nature, 2020)
The aim of this study was to evaluate the population structure of Brazilian buffaloes using of pedigree information. The pedigree used in the analyses included records of 16,915 animals. The population parameters were obtained through the ENDOG software. The estimates of mean of inbreeding (F) and average relatedness (AR) coefficients were 3.22% and 5.99%, respectively. The average generation interval was 6.39 years. The effective number of founders and ancestors was 28 and 22, respectively. In this study, we concluded that the selection of individuals with lower AR is necessary to avoid an increase in matings between inbreeding individuals in this population, in order to obtain greater genetic gain by selection.
Keywords: Dairy buffaloes; Genetic variability; Inbreeding